The Impact of Workload, Work Environment and Work Conflict on Work Stress Among Employees - Muhamad Dedi Irwansah; Nurleila Jum’ati; Dwi Prihantono (International Forum of Researchers and Lecturers, 2024)
This research aims to test and analyze the effects of workload, work environment, and work conflict on work stress among employees. The analysis unit in this study consists of 36 employees. Samples were taken using saturated sampling techniques. Data analysis was conducted using statistics with the help of SPSS version 22. Based on the results of the data analysis using the t-test, it is known that partially, workload has a significant effect on work stress, the work environment has a positive and significant effect on work stress, and work conflict has a positive and significant effect on work stress. Meanwhile, based on the results of the data analysis using the F-test, it is known that simultaneously, workload, work environment, and work conflict significantly affect work stress. Therefore, it is recommended for companies to pay attention to the work environment conditions in order to reduce employees' work stress.